2021
DOI: 10.1186/s42506-021-00097-8
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic risk factors and musculoskeletal disorders in bank staff: an interventional follow-up study in Iran

Abstract: Background Long-term use of computer in a static mode may cause musculoskeletal disorders (MSDs) in bank staff. Considering the high number of bank employees in different countries, such as Iran, the risk factors of these disorders should be investigated in order to implement interventions required to reduce the risk factors. This study aimed to examine the risk factors of MSDs using the Rapid Office Strain Assessment (ROSA) method and to perform an ergonomic intervention program with banking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, several scholarly articles have underscored the importance of periodic follow-up assessments to ensure their efficiency and sustainability (Esmaeili et al, 2023;Heidarimoghadam et al, 2020;Lin et al, 2022;Ramdan & Candra, 2021;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021). In terms of sample size or participant selection, certain articles employed mathematical formula to ascertain sample size (Dhole et al, 2021;Heidarimoghadam et al, 2020;Hijam et al, 2020;Lin et al, 2022;Mohammad Yusof et al, 2021;Rostami et al, 2022;So et al, 2019) while others either utilized the inclusion and exclusion criteria (Alghadir et al, 2021;Alipour et al, 2021;Antwi-Afari et al, 2021;Esmaeili et al, 2023;Kee, 2022;Kong et al, 2023;Motamedzadeh et al, 2021;Rahman et al, 2019;Ramdan & Candra, 2021;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021) or did not explicitly specify their sampling approach (Anshasi et al, 2022;Arunkumar et al, 2019;Darliana et al, 2020). Further analysis of the years of publication showed that a total of nine articles were published in 2021, which was the highest between 2018 to 2023.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis revealed that 9(64.3%) and 5(35.7%) hospitals had acceptable and moderate levels of preparedness in response to biological incidents, respectively. In studies that assess hospital preparedness for biological incidents, different tools have been used for this purpose, each of which evaluates various indicators of preparedness [4,[26][27][28][29][30][31][32][33][34]. Moreover, available tools cannot provide accurate and reliable indicators to estimate hospital preparedness in response to biological incidents [35].…”
Section: Hospital's Codementioning
confidence: 99%